The relative strengths of rapid and delayed density dependence acting on a terrestrial herbivore change along a pollution gradient - Mark D. Hunter; Mikhail V. Kozlov (Blackwell Publishing Ltd, 2022)
Animal populations vary in response to a combination of density‐dependent and density‐independent forces, which interact to drive their population dynamics. Understanding how abiotic forces mediate the form and strength of density‐dependent processes remains a central goal of ecology, and is of increasing urgency in a rapidly changing world.
Here, we report for the first time that industrial pollution determines the relative strength of rapid and delayed density dependence operating on an animal population. We explored the impacts of pollution and climate on the population dynamics of an eruptive leafmining moth, Phyllonorycter strigulatella, around a coal‐fired power plant near Apatity, north‐western Russia. Populations were monitored at 14 sites over 26 years.
The relative strengths of rapid and delayed density dependence varied with distance from the power plant. Specifically, the strength of rapid density dependence increased while the strength of delayed density dependence decreased with increasing distance from the pollution source. Paralleling the increasing strength of rapid density dependence, we observed declines in the densities of P. strigulatella, increases in predation pressure from birds and ants, and declines in an unknown source of mortality (perhaps plant antibiosis) with increasing distance from the power plant.
In contrast to the associations with pollution, associations between climate change and leafminer population densities were negligible.
Our results may help to explain the outbreaks of insect herbivores that are frequently observed in polluted environments. We show that they can result from the weakening of rapid (stabilizing) density dependence relative to the effects of destabilizing delayed density dependence. Moreover, our results may explain some of the variation reported in published studies of animal populations in polluted habitats. Variable results may emerge in part because of the location of the study sites on different parts of pollution gradients. Finally, in a rapidly changing world, effects of anthropogenic pollution may be as, or more, important than are effects of climate change on the future dynamics of animal populations.